The Effect of Price And Service Quality on Consumer Satisfaction With Purchasing Decisions As Mediating Variables on Alfamart Consumers - Muinah Fadhilah; Agus Dwi Cahya; M. Jurais Ardiansyah (Economos : Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of price and service quality on consumer satisfaction with purchase decisions as a mediating variabel on Alfamart consumers. The sampling technique used the Lemeshow formula. Data were obtained by distributing questionnaires about price, service quality, purchasing decisions, and consumer satisfaction to 130 respondents. The data analysis technique in this study is the Structural Equation Model (SEM) using the AMOS application. The results showed: 1) Price and service quality had a positive and significant effect on consumer satisfaction at Alfamart consumers. 2) Price and Service Quality have a positive and significant effect on purchasing decisions for Alfamart consumers. 3) Price and Service Quality have a positive and significant effect on Alfamart consumer satisfaction through the buyer's decision variabel as an intervening variabel. 4) Purchase decisions affect consumer satisfaction at Alfamart consumers.